Pharmacokinetics and pharmacodynamics of acetylsalicylic acid after intravenous and oral administration to healthy volunteers - Nagelschmitz J; Blunck M; Kraetzschmar J; Ludwig M; Wensing G; Hohlfeld T (Dove Medical Press, 2014)
J Nagelschmitz,1 M Blunck,1 J Kraetzschmar,1 M Ludwig,1 G Wensing,1 T Hohlfeld2 1Bayer HealthCare AG, Clinical Pharmacology, Wuppertal, Germany; 2Institut für Pharmakologie und Klinische Pharmakologie, Heinrich-Heine Universität Düsseldorf, Düsseldorf, Germany Background: The pharmacology of single doses of acetylsalicylic acid (ASA) administered intravenously (250 or 500 mg) or orally (100, 300, or 500 mg) was evaluated in a randomized, placebo-controlled, crossover study. Methods: Blood and urine samples were collected before and up to 24 hours after administration of ASA in 22 healthy volunteers. Pharmacokinetic parameters and measurements of platelet aggregation were determined using validated techniques. Results: A comparison between administration routes showed that the geometric mean dose-corrected peak concentrations (Cmax/D) and the geometric mean dose-corrected area under the curve (AUC0–∞/D) were higher following intravenous administration of ASA 500 mg compared with oral administration (estimated ratios were 11.23 and 2.03, respectively). Complete inhibition of platelet aggregation was achieved within 5 minutes with both intravenous ASA doses, reflecting a rapid onset of inhibition that was not observed with oral dosing. At 5 minutes after administration, the mean reduction in arachidonic acid-induced thromboxane B2 synthesis ex vivo was 99.3% with ASA 250 mg intravenously and 99.7% with ASA 500 mg intravenously. In exploratory analyses, thromboxane B2 synthesis was significantly lower after intravenous versus oral ASA 500 mg (P<0.0001) at each observed time point up to the first hour after administration. Concentrations of 6-keto-prostaglandin1α at 5 and 20 minutes after dosing were also significantly lower with ASA 500 mg intravenously than with ASA 500 mg orally. Conclusion: This study demonstrates that intravenous ASA provides more rapid and consistent platelet inhibition than oral ASA within the first hour after dosing. Keywords: intravenous acetylsalicylic acid, oral acetylsalicylic acid, pharmacodynamics, pharmacokinetics, platelet aggregation, cyclooxygenase-1, thromboxane formation